Identifying patient concerns during consultations in tertiary burns services: development of the Adult Burns Patient Concerns Inventory. Issue 12 (30th December 2019) - Gibson, John Alexander Gerald; Yarrow, Jeremy; Brown, Liz; Evans, Janine; Rogers, Simon N; Spencer, Sally; Shokrollahi, Kayvan
Abstract : Objectives: Identifying the issues and concerns that matter most to burns survivors can be challenging. For a number of reasons, but mainly relating to patient empowerment, some of the most pressing concerns patients may have during a clinical encounter may not naturally be the focal point of that encounter. The Patient Concerns Inventory (PCI) is a tried and tested concept initially developed in the field of head and neck cancer that empowers patients during a clinical encounter through provision of a list of prompts that allows patients to self-report concerns prior to consultation. The aim of this study was to develop a PCI for adult burns patients. Design: Content for the PCI was generated from three sources: burns health-related quality of life tools, thematic analysis of one-to-one interviews with 12 adult burns patients and 17 multidisciplinary team (MDT) members. Content was refined using a Delphi consensus technique, with patients and staff members, using SurveyMonkey. Setting: Within outpatient secondary care. Participants: Twelve adult burns patients and MDT members from two regional burns centres. Results: A total of 111 individual items were generated from the three sources. The Delphi process refined the total number of items to 58. The main emergent domains were physical and functional well-being (18 items), psychological, emotional and spiritual well-being (22 items), social care and social well-being (7 items) and treatment-related concerns (11 items). Conclusions: The Adult Burns Patient Concerns Inventory is a 58-item, holistic prompt list, designed to be used in the outpatient clinic. It offers a new tool in burn care to improve communication between healthcare professionals and patients, empowering them to identify their most pressing concerns and hence deliver a more focused and targeted patient-centred clinical encounter.